Conocemos la importancia del autocuidado y la salud para una vida de calidad - Lingn Rubio, Dalia Alexandra (2019)
The present research of professional sufficiency titled Self-care and Health has as purpose sustain and argue by applying a lesson plan to fifth year students of the high school called San Nicolas. The adolescence is a stage of growth and human development, during this stage, the teenager adopts behaviors according to remarkable situations in his daily life which will affect in a good or bad way his self-care practice .Nowadays the adolescent does not know about the great importance of putting in practice self-care for a healthy life. Viewing of this point, the need arises to give the importance of the health self-care to adolescents. For this, It was applied a number of strategies of learning such as motivation, previous knowledge, cognitive conflict and others by using the constructivist approach, which will be used as a tool in a reason for students can get awake the interest in class, with the purpose for the learning to be meaningful._x000D_ Moreover, this research has three parts, the first one has prepared the methodological strategies and didactic process of applying the lesson plan, the second part has the scientific argument with help of bibliographic references and finally psych pedagogical support.